Cultural Contexts of the Formation of Science in the Social-Historical Context of Islamic Countries - Maryam Shamsaei (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Positivist definitions of science defined the relationship between culture and science as an external relationship and considered science free from cultural influences. Still, numerous researches and reflections conducted in the field of sociology and philosophy of science show the effective presence of culture in the context of science. By accepting such an influence, postmodern paradigms consider science as a cultural category and explain the relationship between science and culture in a way that leads to absolute epistemological relativity and the production of science under culture. The following article tries to answer the question of whether cultural contexts affected the formation of science in Islamic societies? The research methodology is focused on the common paradigms in the field of the relationship between science and culture with the documentary method and logical reasoning and in the framework of the philosophy of the cultural system and has finally explained the process of how these two influence each other.